The Moon in the Greek and Roman Imagination : Myth, Literature, Science and Philosophy - Ní Mheallaigh, Karen (Greek Culture in the Roman World Ser, 2020)
Cover -- Half-title -- Series information -- Title page -- Copyright information -- Dedication -- Contents -- Acknowledgements -- List of Abbreviations, Text References and Translations -- Abbreviations -- Note on Text References -- DK, G and LM -- Translations -- Note on Text -- Part I The Moon in the Mythic Imagination -- Introduction: To the Moon! Journey into the Ancient Scientific Imagination -- Chapter 1 The Moon in Ritual, Myth and Magic -- The Moon and Time, Ritual, Religion -- Selene and Endymion: Desire and the Female Gaze -- Lunar Liquid: The Moon-Womb and Proto-philosophy -- Moon-Illusions -- Simaetha's Love-Spell: Magic, Lamps and the Moon -- The 'Thessalian Trick': Magic, Mirrors and the Moon -- The Marriage of Selene and Endymion -- Conclusion -- Part II The Moon in the Scientific Imagination -- Chapter 2 Making Sense of the Moon: Philosophy and Science -- What Is the Moon? The Lunar Artefact -- The Lunar Laboratory: Change and Epistemology -- Heliophotism and the Reflecting Eye -- The Moon Becomes a World -- Metaphysical Moon: The Old Academy and Pythagoreans -- Xenocrates, Philip and the Moon in the Middle -- The Moon in the Pythagorean Cosmos -- Eschatological Moon -- Conclusion -- Chapter 3 Life on the Moon: Between Philosophy, Science and Fantasy -- Pythagorean Moon-Creatures -- The Woman Who Fell to Earth: Helen of Troy -- The Nemean Lion and Other Lunar Creatures -- Conclusion: The Question of Belief -- Chapter 4 The Moon of Many Faces: Plutarch's Great Lunar Dialogue De Facie -- Plutarch's De Facie and the Duel of the Philosophies -- Plutarch's Inter-disciplinary Moon -- The Lunar Texture of De Facie -- Theon, Lamprias and Life on the Moon -- Sulla's Myth: The Moon as Metaphysical Junction -- Literary Coordinates and a Map to the Moon -- Conclusion: A Landmark in the Selenographical Tradition.